2021
DOI: 10.1038/s41587-021-01009-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CRISPR editing with a hypercompact Cas12f1 and engineered guide RNAs delivered by adeno-associated virus

Abstract: Gene therapy would benefit from a miniature CRISPR system that fits into the small adeno-associated virus (AAV) genome and has high cleavage activity and specificity in eukaryotic cells. One of the most compact CRISPR-associated nucleases yet discovered is the archaeal Un1Cas12f1. However, Un1Cas12f1 and its variants have very low activity in eukaryotic cells. In the present study, we redesigned the natural guide RNA of Un1Cas12f1 at five sites: the 5′ terminus of the trans-activating CRISPR RNA (tracrRNA), th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(202 citation statements)
references
References 51 publications
3
153
1
Order By: Relevance
“…Compared to the CRISPR-Cas9 system, the CRISPR-Cas12f system had a clear comparative advantage. The AsCas12f1 used in our work consisted of 422 amino acid residues, as this was one of the high-activity miniature CRISPR-Cas effectors (Kim et al, 2021;Wu et al, 2021). This characterization work demonstrated that the size of the genome editing plasmid was smaller and higher transformation efficiency was obtained in B. anthracis relevant experiments using this effector.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared to the CRISPR-Cas9 system, the CRISPR-Cas12f system had a clear comparative advantage. The AsCas12f1 used in our work consisted of 422 amino acid residues, as this was one of the high-activity miniature CRISPR-Cas effectors (Kim et al, 2021;Wu et al, 2021). This characterization work demonstrated that the size of the genome editing plasmid was smaller and higher transformation efficiency was obtained in B. anthracis relevant experiments using this effector.…”
Section: Discussionmentioning
confidence: 91%
“…Okano et al showed that the Un1Cas12f1 (529 aa) from an uncultured archaeon (Un1) could modify the Escherichia coli genome with high efficiency (50-100%) (Okano et al, 2021). Kim et al showed that an optimized CRISPR/Un1Cas12f1 system enabled efficient and specific genome editing in human cells, with efficiency and specificity similar to that of SpCas9 and AsCas12a (Kim et al, 2021). Wu et al also showed that AsCas12f1 from Acidibacillus sulfuroxidans could serve as an effective genome editing tool in both bacteria and human cells.…”
Section: Introductionmentioning
confidence: 99%
“…The size constraints of the TRV viral vector limit the delivery of large genes such as CRISPR-Cas9. However, it is likely that the continuous development of compact Cas proteins will make it possible in the near future to use TRV to deliver all CRISPR reagents required for genome editing similar to the way adeno-associated viruses are used in human cell lines [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…An alternative solution is to reduce the size of the Cas enzyme, which might make it easier to package alongside the sgRNA in the same delivery system. Several compact nucleases have been reported, including a Cas12j (termed Casϕ) 109 , Cas12f 110 , 111 , Cas13bt 112 and Cas13ct 112 .…”
Section: Therapeutic Rna Payloadsmentioning
confidence: 99%